Industrial effluents boosted antibiotic resistome risk in coastal environments. (January 2023) - Su, Zhiguo; Wen, Donghui; Gu, April Z.; Zheng, Yuhan; Tang, Yushi; Chen, Lyujun
Graphical abstract: Highlights: Coastal area is an ideal platform for studying antibiotic resistome from the "One Health" perspective. Land-based wastewater disposal exports ARGs with higher diversity and abundance to sea. Industrial WWTP effluent might be the source of highest antibiotic resistome risk. mcr-4 and mcr-5 derived from industrial effluent were enriched in the ERA sediments. HGT potential was higher between microbiome of industrial effluent and its ERA sediments. Abstract: Wastewater treatment plants (WWTPs) have been regarded as an important source of antibiotic resistance genes (ARGs) in environment, but out of municipal domestic WWTPs, few evidences show how environment is affected by industrial WWTPs. Here we chose Hangzhou Bay (HZB), China as our study area, where land-based municipal and industrial WWTPs discharged their effluent into the bay for decades. We adopted high-throughput metagenomic sequencing to examine the antibiotic resistome of the WWTP effluent and coastal sediment samples. And we proposed a conceptual framework for the assessment of antibiotic resistome risk, and a new bioinformatic pipeline for the evaluation of the potential horizontal gene transfer (HGT) frequency. Our results revealed that the diversity and abundance of ARGs in the WWTP's effluent were significantly higher than those in the sediment. Furthermore, the antibiotic resistome in the effluent-receiving area (ERA) showed significant difference from that in HZB. For the first time, we identified that industrial WWTP effluent boosted antibiotic resistome risk in coastal sediment. The crucial evidences included: 1) the proportion of ARGs derived from WWTP activated sludge (WA) was higher (14.3 %) and two high-risky polymyxin resistance genes ( mcr-4 and mcr-5 ) were enriched in the industrial effluent receiving area; 2) the HGT potential was higher between resistant microbiome of the industrial effluent and its ERA sediment; and 3) the highest resistome risk was determined in the industrial effluent, and some biocide resistance genes located on high-risky contigs were related to long-term stress of industrial chemicals. These findings highlight the important effects of industrial activities on the development of environmental antimicrobial resistance.